Effective SOP writing - Brown, Laura (Henry Stewart Talks, 2013)
The process of writing an SOP, Key considerations for writing an SOP, Managing cultural differences, Approaches for writing SOPs, Effective SOP writing team, Review draft, Editing, Finalization, Implementation, Distribution and control, Retrieval of SOPs, Good English style, Translating activities into SOPs, Level of detail